The Dialektika Ijtihad, Inovasi, dan Kejujuran Akademik dalam Pembelajaran Ilmu Al-Qur’an dan Tafsir: Studi Kualitatif di STIQ Kepri - Sufyan Muttaqin (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This research aims to analyze the dialectics of ijtihad, innovation, and academic honesty in the learning process of Qur’anic Studies and Tafsir at Sekolah Tinggi Ilmu Al-Qur’an Kepulauan Riau. The study employed a descriptive qualitative approach with a case study design. Data were collected through observation, in depth interviews, and documentation involving three lecturers of Qur’anic Studies and Tafsir, three final semester students, and two academic leaders. The findings reveal that the practice of academic ijtihad develops through critical discussions, comparative tafsir studies, and contextual analytical assignments. Learning innovation is manifested through the utilization of digital technology, interactive thematic discussions, collaborative learning, and mini research-based learning. The implementation of academic honesty is carried out through the habituation of scientific citation, originality assessment of assignments, and academic integrity development. The findings indicate that ijtihad, innovation, and academic honesty have a dialectical relationship that mutually reinforces one another in shaping critical, adaptive, and integrity-based tafsir learning. This study contributes to the development of an epistemologically integrated learning model for Qur’anic Studies and Tafsir in Islamic higher education institutions.